O-068 Direct mechanical thrombectomy with or without bridging thrombolysis in patients with acute ischemic stroke: a systematic review and meta-analysis of randomized trials. (23rd July 2022) - Morsi, R; Carrión-Penagos, J; Desai, H; Tannous, E; Kothari, S; Khamis, A; Tarabichi, A; Bastin, R; Hneiny, L; Thind, S; Coleman, E; Brorson, J; et al.
Abstract : Introduction/Purpose: Current published guidelines and meta-analyses comparing direct mechanical thrombectomy (MT) alone versus MT with bridging intravenous thrombolysis suggested that MT alone is non-inferior to MT with bridging thrombolysis in achieving favorable functional outcome. Because of this controversy, we aimed to systematically update the evidence and meta-analyze data from randomized trials comparing MT alone versus MT with bridging thrombolysis. Materials and Methods: We searched three databases, MEDLINE (through Ovid), EMBASE, and the Cochrane Library from inception to December 14, 2021, to identify randomized trials comparing clinical outcomes, including favorable functional outcome and mortality at 90 days, successful reperfusion, defined as modified TICI score ≥2b, and symptomatic intracranial hemorrhage (sICH), between those who underwent MT alone and those who underwent MT with bridging thrombolysis. We pooled and reported the incidence of these outcomes and calculated the measures of association by risk ratio (RR). We assessed the certainty of the evidence using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach, and the risk of bias of all included studies using the Cochrane risk-of-bias tool (RoB). Results: Out of 11, 109 citations, we identified 51 eligible studies, and included six studies: two post-hoc analyses of randomized trials, and four randomized trials. The total number of patients included was 2, 305. The age (years) of the subjects was 69.97 ± 12.28 (mean ± SD). All studies used intravenous alteplase (0.6 – 0.9 mg/kg bolus) for thrombolysis. When comparing MT alone versus MT with bridging, we found no statistically significant difference in favorable functional independence (RR, 1.07; 95% CI, 0.94, 1.21), mortality at 90 days (RR, 0.83; 95% CI, 0.66, 1.06), successful reperfusion (RR, 1.04; 95% CI, 1.00, 1.07), or sICH (RR, 1.17; 95% CI, 0.84, 1.64). Risk of bias was high across all identified studies. Conclusion: Our meta-analysis showed that adjunctive therapy with intravenous thrombolysis may not provide added benefit to patients undergoing mechanical thrombectomy in terms of functional outcome, mortality, successful reperfusion, or symptomatic bleeding, which is consistent with previous analyses. Further research is needed to clarify which patient subgroups would benefit from either modality. Disclosures: R. Morsi: None. J. Carrión-Penagos: None. H. Desai: None. E. Tannous: None. S. Kothari: None. A. Khamis: None. A. Tarabichi: None. R. Bastin: None. L. Hneiny: None. S. Thind: None. E. Coleman: None. J. Brorson: None. S. Mendelson: None. A. Mansour: None. S. Prabhakaran: None. T. Kass-Hout: None.